First record of Peropteryx pallidoptera (Chiroptera: Emballonuridae) in Bolivia - Siles, Lizette; Hidalgo-Cossio, Marisol; Amusquivar-Calustro, Alejandra; Camacho, Teodoro; Huayta-Sarzuri, Gabriela (Therya Notes, 2021)
The genus Peropteryx contains five species distributed in the Neotropical region. Three of these species occur in Bolivia (P. macrotis, P. kappleri, and P. leucoptera). The recently described Peropteryx pallidoptera is distributed in the Amazonian lowland forests of Ecuador, Perú, Brazil, and Colombia. We report the first record of P. pallidoptera in Bolivia. On November 22, 2016, we observed a bat colony in a ground cavity, in a forest patch located in the rural community of Isinuta in Chapare Province (Cochabamba Department). The area is classified as southwestern Amazonian forests ecoregion. We collected one specimen and confirmed the identification of the species with skull measurements. We observed all external and cranial diagnostic characters of P. pallidoptera in our specimen. Also, the external and cranial measurements are within the range reported for the species. Our specimen extends the known distribution of P. pallidoptera 1,420 km to the southeast from the nearest point in Perú, and it is the southernmost locality for the species. The habitat type and roost where we collected P. pallidoptera is consistent with the descriptions in the literature. Our new record in Bolivia is within the potential wide distribution in the Amazon region predicted in the species description. However, it creates a large gap in northern Bolivia, northwestern Brazil, and southeastern Perú where more records should be expected in the future.